Strategies for Building Children's Religious Character in Foster Homes and Modern Tahfiz Institutions - Nurfathiyah, Aisyah; Akbar, Ali (Madania: Jurnal Ilmu-Ilmu Keislaman, 2024)
Religious character is essential for children to navigate the challenges of rapid societal changes and moral degradation. This study aims to analyze the strategies employed in fostering religious character development in children at educational institutions, such as foster homes and modern Tahfiz institutions. The research utilizes a qualitative descriptive approach, with data collected through interviews, observations, and documentation. The analysis involves data reduction, presentation, and conclusion drawing. The findings reveal that the strategies implemented by the Yakesma Modern Tahfiz and Foster Home in Medan include religious mentoring, character education, motivational guidance, fostering independence and discipline, and promoting social interactions. Supporting factors, such as adequate facilities and skilled caregivers, play a crucial role, while challenges arise from children's unstable emotional development. These strategies effectively shape the religious character of children, equipping them to face future societal challenges with resilience and moral integrity.